Relationships between self-reported asthma and pulmonary function and various measures of obesity. (3rd July 2018) - Myung, Jaeeun; Lee, Hyeain; Kim, Tae Hyun; Han, Euna
ABSTRACT: Objective : We explore the association with self-reported asthma and pulmonary function based on spirometry measurements using different measures to determine obesity because body mass index (BMI) is limited in not differentiating fat and muscle mass. Methods : A multi-year cross-sectional study using Korean National Health and Nutrition Examination Survey data was conducted between July 2008 and May 2011. A total of 9409 subjects were included in the final analysis. Results : Obesity was associated with self-reported asthma and pulmonary function limitations mainly in adult women aged between 40 and 65 years and elderly men aged 65 or older. The association was stronger when the measurement of obesity was based on body fat percentage or waist-to-height ratio (WHtR), compared to BMI. There was a higher self-reported asthma risk among obese women according to the WHtR [odds ratio (OR) = 1.817, 95% CI: (1.208, 2.735)]. There was an increased risk of pulmonary function limitation with abdominal obesity [OR 1.418, 95% CI (1.020, 1.972)], weight-to-height ratio [OR 1.467, 95% CI (1.058, 2.034)], and obesity with regard to body fat percentage [OR 1.753, 95% CI (1.251, 2.457)] in adult women. In elderly men, obesity based on body fat percentage was associated with an increased risk of pulmonary function limitation [OR 1.93, 95% CI (1.098, 3.388)]. Conclusions : Measures other than BMI should be examined when investigating the effect of obesity on self-reported asthma and pulmonary function limitation.